The Requirement of Applying the Excellence Management in Kindergarten organizations in Damascus City (Damascus University Journal of educational and Psychologyical sciences, 2021)
The research aimed at identifying the requirement of applying the Excellence Management in Kindergarten organizations in Damascus City, and Knowing the differences between the mean scores of the individual sample on the scale regarding the variable of dependence, the scientific qualification and years of service. To achieve this aim the research depended on the descriptive analytical approach. The Scale(inventory) was applied on a random  sample(200) of female Kindergarten Principals in Damascus City. The questionnaire was applied to achieve the aim. The research results Showed that the requirements were identified in four domains which are (strategic construction, human resources development, effective leadership, and Local society service). The results showed that the need for them with a high degree. The results also Showed that there were differences of statistical significance at the level(0.05) between the mean scores of Kindergarten principals according to the variable of Kindergarten dependence in the total degree in favour of public and private Kindergartens. The results also indicated that there were statistically significant differences at the level (0.05)between the mean scores of Kindergarten principals according to the scientific qualification variable in the total degree in favour of kindergarten principals with the scientific qualification "Institute, BA and more". The results also indicated that there was no statistical difference of significance at the level (0.05) between the mean scores of Kindergarten principals in the total score of the inventory and the secondary branches due to the variable of Years of service which were not significant in all dimensions.
Keywords: The Requirement of Applying the Excellence Management in Kindergarten organizations in Damascus City